PENGARUH SEBARAN KLOROFIL-A TERHADAP HASIL TANGKAPAN IKAN CAKALANG (KATSUWONUS PELAMIS) PADA PENGOPERASIAN PURSE SEINE DI PERAIRAN ACEH - M_Habib_Ey M_Habib_Ey; Nofrizal_nofrizal Nofrizal_nofrizal; Mubarak_mubarak Mubarak_mubarak (Fakultas Perikanan dan Kelautan, Universitas Riau, 2018)
Aceh Waters has a very potential biological resources, that made the cathing rates become the potential activities. Skipjack Tuna (Katsuwonus pelamis) is one of the potential fishing due to high economic value and its high distributions. The abundant of Skipjack Tuna was affected by the productivities of chlorophyll-a. this study aims to investigate the effects of chlorophyl-a on the catch rates of Skipjack Tuna in Aceh waters during September 2017. Survey methods were applied for this study by conducting three scientific research cruises to 32 fishing ground stations. The results of satellite images and catch retes were generate by using overlay method. Satellite images data on September 2017 shows that the average of chlorophyll-a is around 0,23 mg/m3, with the variations 0,10 – 1,30 mg/m3 that distributed around Aceh Waters and Selat Melaka. And the biggest catching of Skipjack Tuna achieved on the third trip where the chlorophyll-a is around 0,17mg/m3 and the total of catch rates is 7,480 kg.